Pengembangan Model Pembelajaran PAI Berbasis Ekstrakurikuler - Yoyoh Badriyyah (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2019)
There are many efforts made by schools in efforts to develop Islamic Education learning in schools. However, sometimes these efforts are still unable to solve the problems that arise in schools. Management of extracurricular programs in schools requires a well-planned and comprehensive design that includes all learning components. Because these learning components contribute to the success rate of the implementation of learning. Krida Nusantara, as a public-based school has shown a model in the development of Islamic Education learning in public schools, namely through an integrated approach with well-managed extracurricular religious programs. The results of this study show that the success of implementing Islamic Education learning in schools is supported by the extracurricular religious education program. (penag) which is well designed and implemented, starting from the aspects of learning design (learning objectives, teaching materials, process and evaluation), management staff (religious leaders), teaching staff, and controlling learning constraints. Abstrak Banyak upaya yang dilakukan sekolah dalam upaya pengembangan pembelajaran PAI di sekolah. Namun upaya-upaya tersebut terkadang masih belum mampu mengatasi persoalan yang muncul di sekolah. Pengelolaan program ekstrakurikuler di sekolah dibutuhkan suatu desain yang terencana dengan baik serta komprehensif mencakup seluruh komponen-komponen pembelajaran. Sebab komponen-komponen pembelajaran tersebut ikut andil mempengarhui tingkat keberhasilan pelaksanaan pembelajran. Krida Nusantara, sebagai sekolah yang berbasis umum telah menunjukan sebuah model dalam pengembangan pembelajaran PAI di sekolah umum yaitu melalui pendekatan inegrasi dengan program ekstrakurikuler keagamaan yang terkelaola dengan baik.hasil penelitian ini menunjukan bahwa keberhasilan penyelenggaraan pembelajaran PAI di sekolah karena ditunjang oleh program ekstrakurikuler pendidikan agama (penag) yang dirancang dan dilaksanakan dengan baik, mulai dari aspek desain pembelajaran (tujuan pembelajaran, materi ajar, proses dan evaluasi), tenaga pengelola (pamong agama), tenaga pengajar, serta pengendalian kendala pembelajaran.